Parameter study on the influence of a radial groove design on the drag torque of wet clutch discs in comparison with analytical models. (March 2018) - Neupert, Thomas; Benke, Elisabeth; Bartel, Dirk
Abstract: A considerable part of the power loss in disengaged wet clutches is caused by viscous shearing of the cooling oil between the clutch discs. Reducing this drag loss as far as possible is the objective of current research. This contribution deals with the measurement and analytical computation of the drag torque of a clutch disc with radial grooving. Operating parameters and diverse geometrical parameters such as groove width, depth, angle, or number are varied. A newly developed single-disc test rig by which the dependencies of the drag torque are able to be examined is used for measuring. Conclusions to the cause of the fluid flow behaviour are drawn and the results are compared to analytical calculation models. Highlights: Structure and function of a new developed test rig is presented. The drag torque in dependence on the operating parameters can be determined exactly. Influence of geometrical groove parameters on drag torque is clearly determinable. The obtained measurement data is compared with four different analytical models.